FACTORS THAT MOTIVATE OR OBSTACLE THE IMPLEMENTATION OF ENVIRONMENTAL EDUCATION IN THE CONTEXT OF SPECIAL EDUCATION: OPINIONS OF GENERAL AND SPECIAL EDUCATION TEACHERS - Loukas, Moustakas; Mania, Phaedra (International Journal of Research -GRANTHAALAYAH, 2021)
The present study attempts to investigate the views of general and special education teachers regarding those factors that motivate and hinder the implementation of Environmental Education (E.E.) in the context of Special Education (S.E.). It is a quantitative research for the needs of which a questionnaire was created based on the theoretical framework of the study in order to be given to teachers on the island of Rhodes. From the analysis of the results it was found that the main factors that can motivate the implementation of the E.E. in the context of S.E. is the willingness of teachers to implement innovative programs (such as E.E.), the benefits arising from the implementation of E.E. to the students with special educational needs and/or disabilities, the personal interest of the teachers in E.E., their environmental education, the acquisition of knowledge about environmental issues and the adequate training of the teachers in subjects of P. Ε. and E.A. On the other hand, the most important factors that can hinder its implementation are the lack of time/inflexibility of the program, the bureaucratic process for the approval of the program, the lack of material and technical equipment, the lack of training of teachers in the subject of E.E. and the workload of teachers.